An Intrusion Detection System for Malicious Attacks in Cloud Environment Using Decision Tree Techniques - Gopala, B; Hanumanthappa, M (International Journal of Computer Sciences and Engineering, 2025)
Secured and reliable services in cloud computing environment is an important issue. A sensitive data in a cloud computing environment is major issues with regard to security in a cloud based system. Many cloud service providers obtain server from other service providers due to it is cost affective and flexible for operation which makes way for data stolen from the external server. To counter a variety of attacks, especially large-scale coordinated attacks, this paper provides a framework for identifying intrusions in cloud environment using Decision Tree Techniques. The proposed system could reduce the impact of these kinds of attacks through providing timely notifications about new intrusions to Cloud users’ systems